2018
DOI: 10.1155/2018/4514329
|View full text |Cite|
|
Sign up to set email alerts
|

The Anti-Inflammatory Effects of Shinbaro3 Is Mediated by Downregulation of the TLR4 Signalling Pathway in LPS-Stimulated RAW 264.7 Macrophages

Abstract: Shinbaro3, a formulation derived from the hydrolysed roots of Harpagophytum procumbens var. sublobatum (Engl.) Stapf, has been clinically used in the pharamacopuncture treatment of arthritis in Korea. In the present study, Shinbaro3 inhibited NO generation in LPS-induced RAW 264.7 cells in a dose-dependent manner. Shinbaro3 also downregulated the mRNA and protein expression of inflammatory mediators in a dose-dependent manner. Three mechanisms explaining the effects of Shinbaro3 in RAW 264.7 cells were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…TNF-α, IL-6, IL-1) and chemokines (viz. MCP-1) 6 , 35 , 70 , 71 and microglial pro-inflammatory (M1) polarization 72 , but the TLR4/TRIF signal may be anti-inflammatory and neuroprotective 73 76 .…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α, IL-6, IL-1) and chemokines (viz. MCP-1) 6 , 35 , 70 , 71 and microglial pro-inflammatory (M1) polarization 72 , but the TLR4/TRIF signal may be anti-inflammatory and neuroprotective 73 76 .…”
Section: Discussionmentioning
confidence: 99%
“…Mouse macrophage RAW 264.7 cells obtained from the American Type Culture Collection (ATCC, Rockville, MD, USA) were cultured in Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 10% heat-inactivated fetal bovine serum (FBS) with antibiotics-antimycotics (PSF; 100 units/mL penicillin G sodium, 100 ng/mL streptomycin, and 250 ng/mL amphotericin B) [26,27]. The cells were seeded in 24-well plates (2 × 10 5 cells/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have revealed that many anti-inflammatory drugs affect the TLR4/MyD88/NF-κB pathway. Chung et al [30] demonstrated that Shinbaro3 modulates the TLR4/MyD88 pathway to exert anti-inflammatory effects in LPS-stimulated RAW 264.7 macrophage cells. Jia et al [31] reported that berbamine exerts anti-inflammatory effects via the inhibition of the NF-κB and MAPK signalling pathways.…”
Section: Discussionmentioning
confidence: 99%